Asset pricing with liquidity risk: Evidence from a Frontier Market - Herath, H.M.K.M.; Samarakoon, S.M.R.K. (University of Jaffna, 2020)
This study aims to analyze the relationship between stock returns and liquidity risk while taking into account the time-varying characteristics of 1 illiquidity on the Colombo Stock Exchange from 2015-2019 and taking into account the effect of liquidity level, using the Generalized Method of Movements (GMM) framework model to assess the persistence of illiquidity stocks. The updated version of Amihud Illiquidity (Amihud, 1986) is a contribution that represents illiquidity and research across the time-series relationship between liquidity and return. The price of liquidity risk and its effect on expected returns are tested empirically using the conditional liquidity adjusted capital asset pricing model (LCAPM), where stock returns are cross-sectionally dependent on market risk and three additional betas (𝛽 1 , 𝛽 2 , 𝛽 3 ) that capture different aspects of illiquidity and its risk. The results show some support for the conditional capital asset pricing model (CAPM), but the results are not robust to alternative requirements and estimation methods. The total effect of liquidity risk is 0.11%, and illiquidity is 2.5% per year. The total annualized illiquidity premium is therefore found that 2.61% in the Colombo stock exchange.
Keywords: asset pricing; Colombo Stock Exchange; generalized method of movements and liquidity risk